Analisis Preferensi Konsumen Terhadap Atribut Produk Katering Sehat Di Kota Malang - Rianzani, Dian Muji; Rayesa, Neza Fadia; Andriani, Dwi Retno (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2025)
This research aimed to analyze consumer preferences for healthy catering product attributes, including taste, calories, nutritional information, price, menu combinations, packaging, raw material quality, additional services, and halal certification labels. The research uses a descriptive quantitative method with conjoint analysis, where data processing is carried out through the Statistical Package for the Social Sciences (SPSS). Data were collected through questionnaires to respondents who had purchased heatlhy catering. A total of 100 respondents were successfully coected as research sampes. The resuts show that consumer preferences for healthy catering product attribute combinations are Indonesian taste, row calories (≤ 400 kcal), complete nutritional information, price ≤ Rp 35,000, three menu combinations, reusable packaging, organic raw material quality, nutritional consultation services, and halal certification labels. The nutritional information attribute has the highest level of importance (23,699). This study recommends developing product attributes, especially nutritional information and low-calorie menu variations, as we as utilizing social media and targeting advertisements at private employees to expand market reach. Future researchers are advised to expand the scope of the attributes studied.